Formal Mentoring and Teachers’ Effectiveness in Stress Management in Private Secondary Schools in Awgu Education Zone of Enugu State, Nigeria (Journal of Pharmaceutical Negative Results, 2022)
The study examined the effect of formal mentoring on teachers’’ effectiveness in stress management in private secondary schools in Awgu Education Zone of Enugu State, Nigeria. Three research questions and three null hypotheses were formulated to guide the study. Quasi-experimental design using pretest, posttest, and nonequivalent control groups was used. The population of the study consists of all the two hundred and forty teachers who have served for not more than five years in private secondary schools. The sample of the study was one hundred and fifty teachers drawn from the total population using Taro Yamane formular, and purposive random sampling was used to select 10 private schools out of the 25 government approved private secondary schools. Two researchers developed instruments: Teachers Mentoring Guide (TMG) and Teachers’ Stress Management Effectiveness Questionnaire (TSMEQ) were used to gather data. Data collected were analyzed using mean and standard deviation to answer the research questions, while the hypotheses were tested using Analysis of Covariance (ANCOVA) at 0.05 level of significance. The results obtained revealed that the teachers who were formally mentored performed more effectively in stress management than those that were not formally mentored. Male teachers performed better in stress management than their female counterpart, and type of mentoring and gender did not have significant interaction effect on effectiveness of teachers in stress management. It is therefore, recommended that formal mentoring of teachers should be introduced in private and public secondary schools to enhance performance of teachers in stress management and overall effectiveness in teaching and learning.